Epigenetic reprogramming of human lung cancer cells with the extract of bovine parthenogenetic oocytes. Issue 9 (30th May 2014) - Wang, Zhenfei; Dao, Rinuo; Bao, Luri; Dong, Yanhua; Wang, Haiyang; Han, Pengyong; Yue, Yongli; Yu, Haiquan
Abstract The tumour suppressor gene silencing and proto‐oncogene activation caused by epigenetic alterations plays an important role in the initiation and progression of cancer. Re‐establishing the balance between the expression of tumour suppressor genes and proto‐oncogenes by epigenetic modulation is a promising strategy for cancer treatment. In this study, we investigated whether cancer cells can be epigenetically reprogrammed by oocyte extract. H460 human lung cancer cells were reversibly permeabilized and incubated with the extract of bovine parthenogenetic oocytes. Bisulphite sequencing showed that bovine parthenogenetic oocyte extract induced significant demethylation at the promoters of the tumour suppressor genes RUNX3 and CDH1, but not at the promoter of the oncogenic pluripotency gene SOX2. Chromatin immunoprecipitation showed that the histone modifications at RUNX3 and CDH1 promoters were modulated towards a transcriptionally activating state, while those at SOX2 promoter towards a transcriptionally repressive state. Correspondingly, bovine parthenogenetic oocyte extract reversed the epigenetic silencing of RUNX3 and CDH1, and repressed the expression of SOX2. At the functional level, proliferation, anchorage‐independent growth, migration and invasion of H460 cells was strongly inhibited. These results indicate that bovine parthenogenetic oocyte extract changes the expression patterns of tumour suppressor and oncogenic genes in cancer cells by remodelling the epigenetic modifications at their promoters. Bovine parthenogenetic oocyte extract may provide a useful tool for epigenetically reprogramming cancer cells and for dissecting the epigenetic mechanisms involved in tumorigenesis.